2D range modulator for high-precision water calorimetry in scanned carbon-ion beams. (19th October 2020) - Holm, Kim Marina; Weber, Ulrich; Simeonov, Yuri; Krauss, Achim; Jäkel, Oliver; Greilich, Steffen
Abstract: Ionization chamber-based dosimetry for carbon-ion beams still shows a significantly higher standard uncertainty than high-energy photon dosimetry. This is mainly caused by the high standard uncertainty of the correction factor for beam quality k Q, Q 0 . Due to a lack of experimental data, the given values for k Q, Q 0 are based on theoretical calculations. To reduce this standard uncertainty, k Q, Q 0 factors for different irradiation conditions and ionization chambers (ICs) can be determined experimentally by means of water calorimetry. To perform such measurements in a spread-out Bragg peak (SOBP) for a scanned carbon-ion beam, we describe the process of creating an almost cubic dose distribution of about 6 × 6 × 6 cm 3 using a 2D range modulator. The aim is to achieve a field homogeneity with a standard deviation of measured dose values in the middle of the SOBP (over a lateral range and a depth of about 4 cm) below 2% within a scanning time of under 100 s, applying a dose larger than 1 Gy. This paper describes the optimization and characterization of the dose distribution in detail.